Assiyasah Ash-Shari’yah, A Model For Administrative and Economic Reforms and Transformations: A Case Study of Umar Bin Abdulaziz Caliphate 717-720 - aliyu ibrahim musaddad (Journal of Islamic Business and Economic Review, 2020)
There is no hesitation that leadership has been given a remarkable domicile and a crucial positioning in Islam, Assiyasah ash-shari’yah is reflected as superlative routine towards a good Governance as well as an ideal model for both political and Economic transformation and reform. This study therefore pursues to search the methods of Umar bin Abdulaziz (R.A) MODE FOR Administrative and economic Reforms and Transformations.The methodology of the study relies on critical and comprehensive analysis of the existing published literature related to the topic. Hence, Data collection is effected through the qualitative method. The findings of this study exposed that there are heaps of mode and wisdoms could be obtaining from the history of caliphate Umar such as his reformations and innovations in governing the state as reflected in his as - siyasahshar’iyyah which can be key to political reform in our modern society. Grounded on the findings, it was suggested that fear of Allah, is the best preference towards the political and Economic reform.